2018
DOI: 10.1097/ico.0000000000001602
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Endothelial Cell Loss on DMEK Grafts After Transplantation in Human Cadaveric Whole Eyes: Description of the Technique and Pilot Study

Abstract: Our proof-of-principle experiment shows that this imaging approach enables quantification of ECL caused by different instruments and surgical techniques after graft implantation. We have used this method to visualize the learning curve of 1 surgeon when learning a new surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although ECL at 6 months postoperatively can be as high as 30% to 40%, reducing ECL before graft transplantation is critical for providing patients with the best possible visual prognosis. 22 Studies in the literature using live cell staining to quantify ECL indicate a wide range, from 7% to 37%, depending on the preparation technique. 7,18,20,23,24 The average ECL of DescePrep-processed tissues evaluated similarly was 7.9%, which may allow for clinical utility and is at the lower end of literature reports for conventional manual dissection, pneumodissection.…”
Section: Discussionmentioning
confidence: 99%
“…Although ECL at 6 months postoperatively can be as high as 30% to 40%, reducing ECL before graft transplantation is critical for providing patients with the best possible visual prognosis. 22 Studies in the literature using live cell staining to quantify ECL indicate a wide range, from 7% to 37%, depending on the preparation technique. 7,18,20,23,24 The average ECL of DescePrep-processed tissues evaluated similarly was 7.9%, which may allow for clinical utility and is at the lower end of literature reports for conventional manual dissection, pneumodissection.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for our results compared to prior studies is that familiarity with the DMEK injection technique has been shown to influence the amount of endothelial cell loss. [ 24 ] The abovementioned studies were performed by surgeons experienced with the injection technique; in our study, an eye bank technician who was naïve to the three injectors performed the stripping and injection of the grafts. The lack of prior experience likely resulted in a higher rate than expected of endothelial loss with the modified Jones tube compared with experienced users.…”
Section: Discussionmentioning
confidence: 99%
“…All these effects contribute to the development of organ dysfunction and death (18). After intraoperative operation, the ECs were damaged, and the body produced stress response and in ammatory factors (19). Therefore, sCD40L level was also increased after operation in patients with non-sepsis.…”
Section: Discussionmentioning
confidence: 99%